A Horticultural Cuticle Supplement Can Impact Quality Characters and Drosophila suzukii Damage of Several Small and Stone Fruit. Issue 4 (14th July 2022) - Tait, Gabriella; Mermer, Serhan; Chave, Ryan D B; Rossi-Stacconi, Marco Valerio; Kaiser, Clive; Walton, Vaughn M
Abstract: Surface wax and other cellular building blocks play an important role in preserving fruit integrity from biotic and abiotic adversities. Huge energy expenses are made by plants to place these protective compounds onto the epidermal cuticle. Sprayable plant and fruit coatings have been developed to protect plant tissues from environmental stresses, pathogens, and arthropods. The aim of this study was to determine if an experimental cuticle supplement containing waxes can affect fruit quality parameters such as firmness and size of various crops. Cherry, blueberry, and winegrape plants treated with the cuticle supplement showed significant increases in berry firmness ranging from 4.6 to 11.6%. No quality benefits were however observed on blackberry. Cuticle supplement applications did not significantly affect berry size. Laboratory trials resulted in a 54% mean reduction in a model pest insect i.e., Drosophila suzukii egg laying on blueberry. Short-duration field trials over 72 ± 2 to 96 ± 2 h on commercial-standard blueberry bushes resulted in 50–93.4% reductions of D. suzukii damage. Longer-term field trials on cherry and blueberry challenged with egg-laying D. suzukii showed reductions of damage ranging from 45 to 95%, up to 30 d after initial cuticle supplement applications. These results indicate that the cuticle supplement significantly alters berry firmness and reduces D. suzukii damage under commercial production conditions. One factor that may contribute to this reduction includes improved fruit quality parameters. The current work serves to expand integrated pest management options to control D. suzukii populations in commercial field settings.